Verdade e historicidade em Heidegger: continuidades e rupturas - Guimaraes, Deborah Moreira [UNIFESP] (2019)
We intend to research how Heidegger thinks of the concept of truth during the 1920s, when he develops his main work, Being and Time (1927), and during the 1930s, when he develops his unpublished work Contributions to Philosophy (Of the Event) (1989). The problem of truth is directly related to Heidegger’s project of a hermeneutic-phenomenological ontology, which confronts the philosophical tradition by challenging different conceptions of truth as adequacy, evidence, and consistency. Heidegger's engagement with Husserl's transcendental phenomenology and Dilthey's historical hermeneutics leads him to the conception of truth as unveiling. Beyond disruptions, we attempt to investigate continuities between Being and Time on one side and Contributions, on the other. We expect to find not a failure in the former, but rather an insufficiency on Heidegger’s questioning of truth. Such insufficiency should be considered within the scope of the transition from the problem of truth to the problem of historicity, since the fields of meaning opened by the world opening existentials are historically constituted. Based on the hypothesis that Being and time must rescue the hermeneutics of the facticity project to consolidate a practical genesis of significance, the objective of this thesis is to explain to what extent historicity becomes the key to read for possible continuities and ruptures. Therefore, this thesis consists of the formulation that the thinking after the turning is capable of realizing the aspirations of existential analytics by realizing that historicity is the basis of the problems of meaning and truth.